New perspectives into the application of Effective Microorganism (EM) on phytopathogenic fungi: in-vitro antioxidant capacity, bioactive substances and fungicidal efficacy - Ahmed Abdelkader Saleh; Mohamed Hamed Elsheikh; Fatma Aly El-Nakieb; Sherien Elsayed Sobhy; Sanaa Soliman Kabeil; Elsayed Elsayed Hafez (Biotechnology & Biotechnological Equipment)
During a series of sampling conducted in Nobaria, El-Beheira, Egypt in 2022 and 2023, defoliation disorders were identified in tomato fields. Three soil samples were collected and subjected to fungal isolation and identification. Molecular analysis revealed the presence of three fungal species, namely Fusarium verticillioides, Fusarium proliferatum and Alternaria tenuissima, with their Genbank accession numbers being OP889680, OP889682 and OP886855, respectively. The efficacy of an effective microorganism (EM) product as an antifungal agent was screened and its bioactive substances were analyzed. The bioactive substances in the EM product included antioxidant compounds, such as phenolics (58 mg/mL) and tannins (17 mg/mL), which contributed to total antioxidant activity of 73% as measured by FRP, PMA and DPPH assays. The EM product was tested for its antifungal activity against the three isolated fungal pathogens. The sensitivity of A. tenuissima, F. verticillioides and F. proliferatum was assessed by measuring the colony growth when exposed to the EM product. It showed concentration-dependent growth inhibition, completely stopping growth at 7% concentration, with inhibition percentages of 93, 100 and 100% for each pathogen. Gene expression in treated fungi was studied, revealing down-regulation of the chitinase gene in F. verticillioides, F. proliferatum and A. tenuissima, compared to controls. Up-regulation of PR4 and PR5 genes was noted in F. verticillioides, while a significant up-regulation of peroxidase and PPO genes was observed in A. tenuissima. This suggests the EM product holds promise as a fungicide alternative.